A Prospective Study of Clinical Features of Anterior Uveitis in Taiwan - Wei-Yu Chiang; Shih-Chou Chen; Shwu-Jiuan Sheu; Hsi-Kung Kuo (Journal of Ophthalmology)
In this study, we reported the patterns, epidemiology, and clinical features of anterior uveitis (AU) in Taiwan, an area of Eastern Asia. This prospective, cross-sectional case series study was performed to identify patients with AU at two tertiary medical centers (Kaohsiung Chang Gung Memorial Hospital and Kaohsiung Veterans General Hospital) located at the southern Taiwan between December 1, 2018, and March 31, 2020. The clinical diagnoses, ocular presentations, and laboratory data, including the results of the aqueous polymerase chain reaction tests, were investigated in these patients. A total of 112 patients, with a mean age of 48.9 years, were included. Most patients (87.5%) presented with unilateral eye disease, with 30 cases of ocular hypertension at the first presentation (27%). The most common clinical diagnoses were idiopathic AU (37.5%), human leukocyte antigen (HLA)-B27-associated acute AU (25.0%), and herpetic AU (18.8%). Among patients with herpetic AU, cytomegalovirus (CMV) was the most common pathogen (17/21, 81%). Compared to HLA-B27-associated acute AU, CMV-related AU was mostly observed in patients that were older in age, exhibited higher intraocular pressure, more keratic precipitates, greater iris atrophy, and more pseudophakia, but was least reported in those with posterior synechiae. This prospective study identified the pattern and clinical features of AU in southern Taiwan.